2001
DOI: 10.1128/jb.183.4.1369-1375.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Metalloprotease Gene Expression in Vibrio vulnificus by a Vibrio harveyi LuxR Homologue

Abstract: Expression of the Vibrio vulnificus metalloprotease gene, vvp, was turned up rapidly when bacterial growth reached the late log phase. A similar pattern of expression has been found in the metalloprotease gene of Vibrio cholerae, and this has been shown to be regulated by a Vibrio harveyi LuxR-like transcriptional activator. To find out whether a LuxR homologue exists in V. vulnificus, a gene library of this organism was screened by colony hybridization using a probe derived from a sequence that is conserved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
92
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 40 publications
7
92
0
Order By: Relevance
“…Without exception, reports issued to date demonstrate that VvpE expression occurs during the late exponential or stationary growth phase. [34][35][36][37] These results evidently indicate that VvpE is not involved in facilitating vulnibactin-mediated iron-assimilation via the proteolytic cleavage of transferrins. DF-HI broth containing HT as an iron source and human body fluids present an iron-limited condition because transferrin-bound iron is not freely available for V. vulnificus.…”
Section: Discussionmentioning
confidence: 89%
“…Without exception, reports issued to date demonstrate that VvpE expression occurs during the late exponential or stationary growth phase. [34][35][36][37] These results evidently indicate that VvpE is not involved in facilitating vulnibactin-mediated iron-assimilation via the proteolytic cleavage of transferrins. DF-HI broth containing HT as an iron source and human body fluids present an iron-limited condition because transferrin-bound iron is not freely available for V. vulnificus.…”
Section: Discussionmentioning
confidence: 89%
“…, it has been suggested that SmcR positively regulates vvpE gene expression in V. vulnificus (10). Thus, to further examine the regulation of vvpE by SmcR, V. vulnificus smcR mutants were constructed by allelic exchange (Fig.…”
Section: Construction and Confirmation Of V Vulnificus Smcr Smcr Crmentioning
confidence: 99%
“…Compared with the substantial number of reports on the characterization of purified elastase, there have been only a few studies on the regulatory mechanism used by the bacterium to modulate the expression of the vvpE gene (9,10). In a previous report, we showed that transcription of the vvpE gene of V. vulnificus is initiated by two different types of promoter, promoter L (PL) 1 and promoter S (PS), in a growth phase-dependent manner (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…could use this system to control many processes including bioluminescence, virulence, mobility, biofilm formation, and extracellular polysaccharide production [32]. Significantly, extracellular proteases, the virulence factors of Vibrio spp., were shown to be regulated by their respective quorum sensing systems, such as hemagglutinin protease hap in V. cholerae [13], metalloprotease empA in V. anguillarum [6], and metalloprotease vvp and cytolysin vvhA in V. vulnificus [25].Vibrio alginolyticus, a ubiquitous organism in seawater, has been isolated from different organisms as part of the normal marine flora. However, it has also been suggested that this species was a pathogen of several marine animals and humans.…”
mentioning
confidence: 99%